Optimal Allocation of Oil Revenues (Case Study: I. R. Iran) - Rouhollah Shahnazi; Rahman Khoshakhlagh; Mohsen Renani (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2012)
Allocation of the oil revenues is one of the most important economic problems in the oil exporting countries budget, so the main aim of this paper is to determine the optimal allocation of oil revenues. This allocation is studied in three sub-problems: the main natural features of oil revenues, effects of ignoring this particular features in policies and the best policy of allocation. In theoretical part, we develop a model based on OLG model of Blanchard (1985) and Uzawa-Lucas endogenous growth model, composition with oil revenues. We analysis the optimal path of consumption, human and physical capital formation and there for the economic growth in four cases with no subsidies, capital subsidies and direct and indirect consumption subsidies (as is the theoretical contribution of this study). In applied part, first we compute the required parameters by using the Iranian economy dataset. Then we calibrate the model constructed in theoretical sector. Finally we solve the model by using Wolfarm Mathematica 6 software. The results indicate the optimal path of consumtion, human and physical capital formation and economic growth is obtained with capital subsidies.